Advancing Sustainable Education: Students' Vocational Fulfillment in Real and Virtual Environments within a Post-Conflict Society - Stoliarchuk, Olesia; Aleksandrova, Olena; Binkivska, Kristina; Serhieienkova, Oksana; Spudka, Iryna; Zabolotniuk, Volodymyr; Turenko, Oleh (European Journal of Sustainable Development, 2025)
This paper analyzes the findings of a study on the attitudes and actions of Ukrainian psychology students regarding the awareness and fulfillment of their calling in real and virtual life spaces through the lens of sustainable development and in the context of a post-conflict society. The phenomenon of calling is viewed as a significant personal construct that not only contributes to successful self-actualization and psychological well-being but also establishes a foundation for sustainable professional development. Examining students' perceptions of the term "calling" is crucial as it enables monitoring, psychological support and the development of competencies essential for sustainable professional growth during their education. An internalized sense of calling is seen as a key to successful professional self-determination in alignment with sustainable development principles, as well as a factor in the effectiveness of further professionalization. It was found that students predominantly perceive calling as an attractive activity that enables them to fulfill their potential while considering social responsibility. Understanding the meanings and functions of calling among future psychologists is vital in the context of providing psychological assistance to clients dealing with difficulties in professional self-fulfillment, career building, and the development of conscious life strategies, particularly in a post-conflict society. The study also revealed that virtual spaces, particularly social networks, serve as a widespread platform for students to realize their calling by seeking relevant and engaging information, fostering social interaction, and expanding communication networks. To mitigate the risks and challenges of the virtual space when understanding and fulfilling their calling, respondents employ critical thinking, a high level of self-respect, adherence to basic cybersecurity principles, information hygiene and sustainable development guidelines Keywords: calling, self-actualization, sustainable development, post-conflict society, future psychologists, virtual space, social networks